All-organic transistors printed on a biodegradable and bioderived substrate for sustainable bioelectronics - Fabrizio A. Viola; Ksenija Maksimovic; Pietro Cataldi; Camilla Rinaldi; Elena Stucchi; Filippo Melloni; Athanassia Athanassiou; Mario Caironi (Materials Today Bio)
Biodegradable electronics is an incipient need in order to mitigate the alarming increase of electronic waste worldwide caused by capillary penetration of electronic devices and sensors. Flexibility, solution processability, low capital expenditure, and energy-efficient processes, which are distinctive features of organic printed electronics, have to be complemented by a sustainable sourcing and end-of-life of materials employed. This requirement calls for solutions where materials, especially substrates that typically represent the largest volume, can be biodegraded in the environment with no harm, yet assuring that no precious resources are dispersed. In this work, the bioderived and biodegradable biopolymer polyhydroxybutyrate (PHB) was used as a substrate, cast from an acetic acid solution, for all-organic field effect transistors (OFETs) based on an inkjet printed polymer semiconductor. The OFETs showed small device-to-device variation, a proper current modulation with ION/IOFF of about 1.2·103, mobility values as high as 0.07 cm2/Vs in saturation regime and channel length/width normalized leakage currents in the order of nA, which remained almost unaltered also after intensive mechanical stresses upon bending and rolling. Such mechanical stability and flexibility, together with the biodegradability and bioderivation, make PHB an appealing candidate for the development of sustainable printed bioelectronics, with widespread future applications in the biomedical and food packaging sector.